Är eller var? Tempusproblem i ordboksdefinitioner - Vilppula, Matti (Nordiske Studier i Leksikografi, 2001)
In definitions of concepts that no more betong ta the present time, dictionaries have sometimes used the present, sometimes the past tense. For instance, highwayman may have been defined as ’one who robs travellers on a public road’ or ’one who robbed travellers on a public road’. Of these two alternatives, the first one should be preferred. If the past tense is used, the definition gets an encyclopedic feature. It suggests that sometirne earlier people were often robbed on the highway. This matter does not belong to the lexical meaning of the word.